Investigating the Relationship Between Self-compassion, Spiritual Well-being, and Marital Satisfaction Among Married University Students: The Mediating Role of Anxiety - Bahareh Bahadori; Parviz Asgari; Farah Naderi (Health, Spirituality and Medical Ethics)
Background and Objectives: Married university students frequently face the dual demands of academic pursuits and personal relationships. Understanding the roles of self-compassion and spiritual well-being in marital satisfaction becomes particularly important in this context. This study examines the relationships between self-compassion, spiritual well-being, and marital satisfaction among married university students, investigating the mediating role of anxiety. Methods: This descriptive-analytical study utilized structural equation modeling (SEM) to examine the hypothesized relationships among self-compassion, spiritual well-being, anxiety, and marital satisfaction. A stratified random sample of 356 married students from Azad University, Ahvaz, Iran, was recruited in 2023. The data were collected using the marital satisfaction scale (MSS), spiritual well-being scale (SWBS), state-trait anxiety inventory (STAI), and self-compassion questionnaire-long form. Statistical analyses were conducted using SPSS software, version 26 and AMOS software, version 26. Results: Self-compassion (β=-0.19, P=0.007) and spiritual well-being (β=-0.11, P=0.008) had significant negative correlations with anxiety. Additionally, self-compassion (β=0.21, P=0.001), spiritual well-being (β=0.10, P<0.020), and anxiety (β=-0.19, P=0.001) were significantly related to marital satisfaction. Bootstrap analyses further confirmed the indirect effects of self-compassion and spiritual well-being on marital satisfaction through anxiety (P=0.013). Conclusion: Self-compassion and spiritual well-being are positively linked to marital satisfaction, likely by reducing anxiety. Encouraging self-compassion and spiritual well-being may improve marital quality.